Integrated information and computing systems for natural, spatial, and social sciences - Ruckemann, Claus-Peter, 1967- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book covers a carefully selected spectrum of issues pertaining to the benefits, dynamism, potential, and challenges of information and computing system application scenarios and components from a wide spectrum of prominent disciplines"--Provided by publisher.